Engineering Geology Of The Mica Underground Powerplant - Alan S. Imrie; Douglas D. Campbell (Society for Mining, Metallurgy & Exploration, 1976)
INTRODUCTION Mica Dam is located on the Columbia River just downstream of the "big bend" of the Columbia, where it leaves the Rocky Mountain Trench and begins to flow southwards, approximately 85 miles north of Revelstoke, B.C. (Fig.l). The dam was built as one of three Columbia River Treaty dams in British Columbia which regulate the flow of the river and provide flood control downstream in Washington and Oregon. In addition, the three Canadian dams make possible greatly increased power generation at existing power plants in the United States and further development along the Columbia and its tributaries in British Columbia. History Mica Dam, constructed during the period 1967 to 1973, is a zoned earthfill embankment 650 feet high, which has 12,000,000 acre feet of live storage and an available head of 550 feet. Power intakes which would serve either a six-unit surface or underground plant were incorporated into the design and construction of the right abutment of the dam (Fig. 2). Prior to 1971 alternative 2500 MW capacity surface and underground powerplant arrangements were studied. Cost estimates for the two alternatives were the same within the limits of estimating procedures. However, it was believed there was a certain continuing risk in locating a surface plant at the toe of a steep canyon wall. Therefore, in 1971 a tentative decision was made to proceed with an underground plant, provided that additional exploration confirmed assumptions of